PENGARUH DIMENSI FRAUD TRIANGLE DAN KOMPETENSI MORAL TERHADAP PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI UNIVERSITAS ISLAM MALANG SELAMA PEMBELAJARAN DARING - Yuni Susanti; Dwiyani Sudaryanti; Arista Fauzi Kartika Sari (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the significant effect of pressure, opportunity, rationalization, and moral competence both simultaneously and partially on the academic cheating behavior of accounting students at the Islamic University of Malang during online learning. All students of the 2018 S1 Accounting Class Faculty of Economics and Business Islamic University of Malang, the researchers set as the population. To take the sample, the researcher used the Probability Random Sampling technique and the researcher used the Yamane formula to determine the number of samples, so that 167 respondents were obtained. This research is classified as quantitative research and data collection uses a survey method, namely by distributing questionnaires. Multiple linear regression analysis became the data analysis method in this study and the tests used were descriptive statistical tests, instrument tests, normality tests, classical assumption tests, and hypothesis testing. The results of the study prove that pressure, opportunity, rationalization, and moral competence have a significant effect either simultaneously or partially on the academic cheating behavior of accounting students at the Islamic University of Malang during online learning.Keywords: Pressure, Opportunity, Rationalization, Moral Competence, and Academic Cheating Behavior.